Effect of Oral Immunostimulation of Humpback Grouper (Cromileptes altivelis) in Increasing Non-specific Immunity to Fight Disease (Review) - Muahiddah, Nuri; Diamahesa, Wastu Ayu (Universitas Syiah Kuala, 2022)
Cromileptes altivelis humpback grouper is a commodity with high economic value. Humpback grouper is Indonesia's main export commodity. The high value of sales and production of humpback grouper is constrained by the many disease attacks in the humpback grouper aquaculture industry. An alternative solution that has been continuously researched for several years to tackle humpback grouper disease is the use of immunostimulants. The use of immunostimulants orally can increase non-specific immunity of humpback grouper to ward off disease attacks and is environmentally friendly. Immunostimulants such as Lactococcus lactis HNL12, Lactococcus lactis HNL12 combined with Schizochytrium limacinum (algae flour), Peptidoglycan, Phycocyanin (Spirulina platensis), Bacterium, Vitamin C, Chromium Yeast, Commercial Yeast can enhance the non-specific immune system in humpback grouper (Cromileptes altivelis). These immunostimulants increase non-specific immunity such as Respiratory burst Activity (RB), superoxide dismutase (SOD), alkaline phosphatase (AKP), lysozyme (LZM), Phagocytosis Activity, Phagocytosis Index, Total leukocytes, hemoglobin, hematocrit, phagocytic activity, lysozyme activity, serum protein, albumin and globulin, total erythrocytes, haemoglobin, hematocrit. These immunostimulants can also prevent attacks of Vibriosis disease caused by the bacteria Vibrio harveyi, Vibrio algynoliticus and Vibrio parahaemolyticus as well as Viral Necrosis Virus (VNN) disease by increasing the survival rate compared to fish that are not given immunostimulants.Keywords: cromileptes altivelis, immunostimulant, non-specific immunity, fish disease